The effectivity of electrode anesthesia in increasing the individual's pain threshold - Esquivel, Josephine F.; Lim, Diana Dorothy A.
This study primarily aims to determine the effectivity of electrode anesthesia in increasing an individual's pain threshold as well as its ability to decrease the incidence of stress related tachycardia. With 30 subjects from the University of the Philippines College of Dentistry, whose ages range from 18 to 22 years who have no systemic disease, the Transcutaneous Electrical Nerve Stimulator (TENS) was applied on the lower premolars, the right serving as the experimental and the left the control, wherein pain threshold values were derived using an Electric Pulp Vitality Tester. (EPVT. Stress related tachycardia was measured by applying a noxious stimulus in the form of a mucosal prick and comparing blood pressure and heart rates obtained after stimulation to baseline blood pressure and heart rate. The acceptability of the machine in terms of procedural manipulation and pain control was derived from questionnaires passed on to the subjects. The results obtained prove that TENS is indeed effective in increasing the individual's pain threshold as well as decreasing stress-related tachycardia. Its acceptability among the subjects tested was overwhelming. All in all, it is hoped that electrical stimulation could someday prove to be an alternative or an adjunct to injectable local anesthetics.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Anesthesia in dentistry